Happiness, Positive Emotions, Cognitive Appraisal, and Coping in University Students of Metropolitan Lima - Loayza-Rivas, José David (2021)
Objective. The main objective of this study was to examine the influence of happiness by cognitive appraisal and positive emotions on stress coping in university students. Method. 352 people participated in the study, 70.2% were women, with an age range of between 19 and 35 years. Structural Equation Models (SEM) were tested to estimate the influence of happiness in the stress process and coping. Results. The results showed expected correlations between the variables and a good fit of the proposed models. Happiness influences the use of adaptive coping strategies, through the cognitive appraisal of challenge (β = .220; p < .001) and the experience of positive emotions (β = .159; p = .001). In conclusion, happiness plays an important role inthe stress and coping process.